Flavonoids and 5-Aminosalicylic Acid Inhibit the Formation of Neutrophil Extracellular Traps - Kirchner, Tina; Hermann, Eva; Möller, Sonja; Klinger, Matthias; Solbach, Werner; Laskay, Tamás; Behnen, Martina (Mediators of Inflammation, 2013)
Neutrophil extracellular traps (NETs) have been suggested to play a pathophysiological role in several autoimmune diseases. Since NET-formation in response to several biological and chemical stimuli is mostly ROS dependent, in theory any substance that inhibits or scavenges ROS could prevent ROS-dependent NET release. Therefore, in the present comprehensive study, several antioxidative substances were assessed for their capacity to inhibit NET formation of primary human neutrophils in vitro. We could show that the flavonoids (−)-epicatechin, (+)-catechin hydrate, and rutin trihydrate as well as vitamin C and the pharmacological substances N-acetyl-L-cysteine and 5-aminosalicylic acid inhibited PMA induced ROS production and NET formation. Therefore, a broad spectrum of antioxidative substances that reduce ROS production of primary human neutrophils also inhibits ROS-dependent NET formation. It is tempting to speculate that such antioxidants can have beneficial therapeutic effects in diseases associated with ROS-dependent NET formation.